Diseño de vigas con el método de los factores de distribución del reglamento AASHTO LRFD - Hurtado Araiza, Alex (My University, 2016)
Diseño de vigas con el método de los factores de distribución del reglamento AASHTO LRFD
Keywords: Diseño de vigas con el método de los factores de distribución del reglamento AASHTO LRFD